2013
DOI: 10.1039/c2py20763j
|View full text |Cite
|
Sign up to set email alerts
|

Design and modification of three-component randomly incorporated copolymers for high performance organic photovoltaic applications

Abstract: Please note that technical editing may introduce minor changes to the text and/or graphics contained in the manuscript submitted by the author(s) which may alter content, and that the standard Terms & Conditions and the ethical guidelines that apply to the journal are still applicable. In no event shall the RSC be held responsible for any errors or omissions in these Accepted Manuscript manuscripts or any consequences arising from the use of any information contained in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 77 publications
3
28
0
Order By: Relevance
“…(a); Table ], due to the decrease of both V oc and FF of the PSCs. It was observed that an increase in the PC 70 BM content resulted in a slight decrease in the V oc , which has been observed for other donor polymers . The reduction in the V oc correlated with the decrease in the energy of the charge transfer (CT) states with increasing PC 70 BM concentrations.…”
Section: Resultssupporting
confidence: 53%
“…(a); Table ], due to the decrease of both V oc and FF of the PSCs. It was observed that an increase in the PC 70 BM content resulted in a slight decrease in the V oc , which has been observed for other donor polymers . The reduction in the V oc correlated with the decrease in the energy of the charge transfer (CT) states with increasing PC 70 BM concentrations.…”
Section: Resultssupporting
confidence: 53%
“…The former is owe to the strong intramolecular charge transfer (ICT) that occurs between donor and acceptor, the latter is attributed to the localized π−π* transition of the polymer backbone . In the past few years, a promising approach was to develop random terpolymers by copolymerizing one electron‐rich unit and two different electron‐deficient units or one electron‐deficient unit and two different electron‐rich units to broaden the absorption spectrum …”
Section: Introductionmentioning
confidence: 99%
“…The copolymerization of this electron-deficient unit with different electron-rich segments has resulted in solar cells with efficiencies up to 8%. 29,[44][45][46][47][48][49][50][51][52] The most promising candidates consist of the conjugation of the DPP moiety to a thienothiophene fragment with a varying number of interconnecting thiophene units. For the simplest case, Meager et al reported PDPP-TT-T based devices with efficiencies >7% for some particular alkyl chain branching position manipulation ( Fig.…”
Section: Diketopyrrolopyrrolesmentioning
confidence: 99%